Agricultural Marketing Reforms: a Conspectus - Paty, BK; Gummagolmath, KC (Journal of Agricultural Extension Management, 2019)
The predominant form of Agricultural Marketing in India is Regulated Marketing. The major objectives of regulated marketing are ensuring correct weighment for the farmers’ produce, prompt payment to the farmers and avoidance of exploitation in the hands of middlemen. The system of regulated marketing has, no doubt, served the purpose in many ways. However, the system has gone through its life cycle and a number of discrepancies have crept into the system in course of time. The system proves to be counterproductive to Processing, Value-addition, Export Promotion, Price Formation, creation of Infrastructure, Private Investment and free movement and storage of Agricultural Produce. It is against this backdrop that in line with the Provisions of Model Act, 2003 of Govt. of India, many states have incorporated a number of changes in their respective State Market Regulating Acts. These reforms have enabled setting up of Private Markets, Contract Farming and Direct Marketing. Other reform measures like Futures Market, empowerment of farmers through wider dissemination of Market Information, Direct Marketing, Retail Chain Linkage, Group Marketing & Farmer Producer Organizations (FP0s) etc. are other timely interventions to make the marketing system vibrant, in harmony with the overall economic environment of liberalisation, privatisation and globalisation. This article is a conspectus and a critique of the reform measures initiated in the Agricultural Marketing Sector of the country, with a focus on bringing about a Marketing perspective in the Agricultural Extension System.